SAMPANG COMMUNITY EMPOWERMENT IN HUMAN CAPITAL THEORY PERSPECTIVE - Astutiek, Dwi (Advances in Social Sciences Research Journal, 2017)
Powerlessness phenomenon in Sampang in this research applying a benchmark of Human Capital theory perspective supported by empowerment concept suggested Friedman and Paulo Feire. This research purposes are : 1. To examine how education program as human capital investment opportunity in order to improving Sampang community empowerment. 2. To find out how contestation of education between formal education and pesantren (Muslim Boarding School) influence the increasing number of illiterate people in the town. Also to find out how hegemonic factors when educational contestation took place. This research yield obtained : first, already found out, to answer the power of Sampang community required known on powerlessness hinder factors previously and will be gained solution from these hindrances. Next applying model from Richard J. Toracco’s Human Capital Theory as implementation of Gery S. Breker’s Human Capital Theory. Second, found the potentials of Sampang people regarding with basic potential as character human, natural potency, social structure potency, cultural potency, religion believe power potency and political potency. Furthermore these potentials can be drawn as supporting factors in realizes human capital theory perspective. Third, found a formula of model development from Richard J. Toracco’s human capital. From the findings above gained as application perspective of human capital theory. Implications of this research outcome are first, in theoretical implications before human capital theory application, is necessary to known in advance empowerment inhibitor factors in region will be developed and solution of exist obstacle all at once. Then using Human Capital theory development suggested by Thomas J. Toracco as perspective of the theory. Second, practical implication are how the role of pesantren be more optimal in preparing their students. The alumnus who have bargain power position (marketable) able to answer mundane and. That is by equipping pesantren education with formal education. Using national language as an introductory language without eliminating local language. Thus will be able to raise Human Development Index (HDI) of Sampang district be better. Third, how empowerment transformation setting through pesantren, formal and nonformal education, serious and focused. Concurrently handling on involvement from various partnership elements engaged. Keywords: community empowerment, human capital theory perspective